Efficacy and safety of Shen-Ling-Bai-Zhu-San combined with chemotherapy for lung cancer: A protocol for systematic review and meta-analysis. Issue 6 (12th February 2021) - Jiang, Jiawang; Li, Zhiming; Zhang, Fenghao; Li, Huaiyu; Li, Renliang; Qiu, Qianjie; Chen, Baoguo
Abstract: Background: Lung cancer (LC), with the high incidence in malignant tumors in the world, and seriously affects people's lives and brings a great economic burden. Previous clinical studies on Shen-Ling-Bai-Zhu-San (SLBZS) combined with chemotherapy for the treatment of lung cancer have been increasing, but there are no systematic reviews. This study aims to systematically study the efficacy and safety of SLBZS combined with chemotherapy in the treatment of LC. Methods: The Chinese and English databases will be searched by us for related documents, and the search time limit is January 2021. Databases including PubMed, Embase, Web of Science, the Cochrane Library, Chinese databases include China National Knowledge Infrastructure, Wanfang Data, ChongqingVIP Information Resource Integration Service Platform, China Biomedical Literature. The international clinical trial registration platform and the Chinese clinical trial registration platform will be searched by us to find ongoing or unpublished trials. After screening the literature based on inclusion and exclusion criteria, 2 researchers independently extracted data. The primary outcomes were the treatment efficiency. RevMan 5.3.5 software will be used for statistical analysis. The Recommendation, Assessment, Development, and Evaluation (GRADE) system will be used to evaluate the quality evidence of each result. Results: This study will provide the latest evidence for the SLBZS combined with chemotherapy for LC. Conclusion: The efficacy and safety of SLBZS combined with chemotherapy for LC will be evaluated. Unique INPLASY number: INPLASY202110025.